Rwanda Economic Update, January 2020 : Accelerating Digital Transformation in Rwanda - World Bank (World Bank, Kigali, 2020)
This edition’s forecast of Rwanda’s economic growth for 2019 is revised upward from the 7.8 percent projected in the REU14 to 8.5 percent. The stronger growth is driven mostly by the unexpected magnitude of the fiscal expansion. Medium-term growth also looks strong with annualgrowth projected to be about 8 percent. Although the current public investment push will continuein the medium-term, this issue’s high growth scenario assumes that the role of the private sector in investment will grow; public investments alone may not sustain growth at 8 percent over themedium-term. The medium-term outlook assumes that debt will accumulate faster than was projected in REU14. The primary explanation is the large fiscal expansion of 2019. Fiscal deficit for 2020 will continue to be well above the historical average. Despite the increasing indebtedness, reliance on concessional financing will help keep Rwanda’s debt sustainable. In the medium term, the CAD will again stay high, hitting 10 percent of GDP. Monetary policy will remain accommodative, although with the return of inflation to the “normal” range and continuing pressures on the exchange rate and reserves, the policy space has narrowed. The risks to Rwanda’s economic outlook, both domestic and external, have risen. The main risk is the growing reliance on public-sectored investments. Fiscal expansion to achieve the government’s targets for expanding access to infrastructure raises the debt, widens external imbalances, and may crowd out access of the private sector to finance, thus undermining long-term growth. If the reliance on the public sector persists, Rwanda may have difficulties in financing its growth model. Rwanda’s commitment toconcessional borrowing and monetary stability reduces the risks to macroeconomic stability, but overall fiscal risks has gone up because of the reliance on the public sector for achieving NST1growth targets. Despite continuing efforts, the ineffectiveness of the private sector remains a major risk to Rwanda’s growth outlook--growth projections for the medium to long term depend on the ability of the private sector to take the lead. As the fiscal expansion for NST1 subsides in the medium term, it will become increasingly difficult to keep the growth rate at 8 percent without increased private sector investment. Now, to achieve sustainable and productivity-led growth, attention must turn to improving allocation of economic resources through better market functioning.